PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL DISCOVERY LEARNING KELAS V SDN 27 ANAK AIR - Putri Indah Mawati Waruwu; Ranti Meizatri; Gita Rahmi; Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning outcomes in Pancasila Education through the implementation of the Discovery Learning model in class V.C of SDN 27 Anak Air, Padang City. This research is a Classroom Action Research (CAR) referring to the Kemmis and McTaggart model, carried out in two cycles, namely cycle I with two meetings and cycle II with one meeting. The research subjects were 23 students, consisting of 10 boys and 13 girls. Data were collected through learning achievement tests, teacher and student activity observation sheets, and teaching module assessment sheets, then analyzed qualitatively and quantitatively. The results showed that: 1) the quality of lesson planning (teaching modules) increased from an average of 87.5% in the good category (B) in cycle I to 100% in the very good category (SB) in cycle II; 2) the implementation of learning on the teacher and student aspects increased from an average of 87.5% (B) in cycle I to 96.9% (SB) in cycle II; 3) student learning outcomes on the attitude aspect increased from 76.09 to 84.51, on the knowledge aspect from 85.99 to 88.76, and on the skill aspect from 75.41 to 86.68. Based on these findings, it can be concluded that the implementation of the Discovery Learning model is effective in improving the quality of planning, implementation, and learning outcomes of students in Pancasila Education in elementary school.